THU0142 The prognosis of heart failure in patients with rheumatoid arthritis. (12th June 2018) - Meissner, Y.; Schäfer, M.; Manger, B.; Zänker, M.; Ochs, W.; Listing, J.; Strangfeld, A.
Abstract : Background: Heart failure (HF) is a condition with high rates of hospital admission and mortality. The impact of rheumatoid arthritis (RA) and its treatment on the prognosis of prevalent HF has been insufficiently studied. Objectives: To evaluate deterioration of HF and mortality in patients with RA and concomitant HF. Methods: The prospectively followed cohort of the German register RABBIT continuously includes RA patients with a new start of a DMARD after at least one csDMARD failure. Among all patients enrolled between 05/2001 and 10/2017 (n=15, 037) patients with prevalent HF were selected (n=393). HF patients were followed until their end of observation or death. Deterioration of HF requiring hospital admission, and death were analysed as composite outcome. Incidence rates (IR) were calculated for current treatment at time of event (9 months risk window after last infusion of rituximab). Generalised estimation equations (GEE) were used to investigate risk factors for the composite outcome. To avoid uncertainties when allocating therapies, only treatment episodes>6 months were included in the GEE analysis. Missing values (DAS28, CRP, physical function) were addressed by multiple imputations. Results: Of the 393 patients with prevalent HF and 1490 patient years (PY) of follow-up, a total of 131 patients had at least one outcome (19 HF deteriorations, 123 deaths). Infections (30%) and cardiovascular events (25%) were most frequently reported as causes of death. The mean time until deterioration/death was 30/35 months. At baseline, patients with an event were older (69 vs. 67 years), more often male (43 vs. 32%), rheumatoid factor positive (80 vs. 74%), had higher CRP-values (39 vs. 23 mg/L) and a worse FFbH (% of physical function: 43 vs. 50) than patients without event. All HF patients had high numbers of comorbidities (mean of 7/6 in patients with/without event). Crude IR were highest in patients under csDMARD only exposure (figure 1). IR were similar during the first 3 or 6 months after start of treatment and thereafter (data not shown). Biologic treatment was not associated with the outcome (table 1). Male gender, higher age, a higher glucocorticoid dose, worse physical function and elevated CRP under treatment were significantly associated with hospitalisation due to HF or a fatal outcome. Conclusions: Patients with RA and HF have an unfavourable prognosis. One third of them were hospitalised for HF or died during follow-up. In addition to patient characteristics, smoking, insufficiently controlled inflammation and treatment with glucocorticoids significantly increased the risk of hospitalisation or death. Acknowledgements: RABBIT is supported by a joint, unconditional grant from AbbVie, Bristol-Myers Squibb, Celltrion, Hexal, Lilly, MSD Sharp and Dohme, Pfizer, Roche, Samsung Bioepis, Sanofi-Aventis und UCB. Disclosure of Interest: Y. Meissner Speakers bureau: Pfizer, M. Schäfer: None declared, B. Manger: None declared, M. Zänker Speakers bureau: Celgene, MSD, Roche, W. Ochs: None declared, J. Listing: None declared, A. Strangfeld Speakers bureau: AbbVie, BMS, Lilly, MSD, Pfizer, Roche, UCB